Memory and Identity in the Time of the Internet: An Autoethnography - Roy, Carole (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes, 2024)
There are moments that define one’s life, and while we never forget them, reflection can lead to new perspectives. In the early 1980s I was part of a long peace march for nuclear disarmament. In 2020, an Internet search for information about this peace march found some documents that provided an impetus for reflection on memory and identity. This autoethnography suggests that unexpected events can provide impetus for critical self-reflection, reflection that honours the search for threads that weave our identity from past to present. This exploration may provide support for future transitions. It also suggests that social movements can be inclusive of a range of people with different levels of knowledge. Finally, it proposes that engagement itself is a source of learning, the impact of which may be understood decades later.